Perspectives of the Obstetric Care Environment for Pregnant Individuals Who Have an Opioid Use Disorder - Samantha Girasulo; Caro Maltz; Maggie Weichert; Joy S. Kaufman; Amanda Mele; Karen Hunkele; Kimberly A. Yonkers; Nancy Byatt; Ariadna Forray (Women's Health Reports)
Objective: To assess the specific barriers and facilitators for pregnant individuals who have an opioid use disorder (OUD) receiving perinatal care. Methods: We conducted key informant interviews with patients who received care from obstetric clinicians who had been trained to provide medication for opioid use disorder (n = 16). We asked patients about the care they received for their OUD, the quality of communication with their perinatal care team, and any recommendations for improving OUD care. Two staff independently coded transcripts, and we used content analysis to identify themes. Results: Our analysis resulted in three main facilitators that support participants receiving care from their obstetric clinician: (1) positive relationship with supportive and nonjudgmental clinician; (2) access to medication for opioid use disorder (MOUD); and (3) access to therapeutic and peer supports. Patients noted that nonjudgmental clinicians provided a care environment where they felt safe, did not experience stigma, and felt they could be active participants in their care. Patients also expressed that access to MOUD and clinical and supportive services were beneficial components of perinatal care. The main barriers identified included lack of access to transportation, long wait times for treatment programs, and difficulty accessing MOUD. Conclusions: The results of this study suggest that increased obstetric provider education about OUDs and providing trauma-informed care for pregnant individuals who have an OUD may help reduce barriers to accessing care and increase satisfaction with care for this population. Furthermore, the present study suggests obstetricians provide in-house access to MOUD, if possible, or assist patients with referrals to care, as these may reduce the structural barriers patients face.